(untitled) (Revista Contexto & Educação, 2025)
Sexual and reproductive health education in the Triple Frontier region, where Brazil, Argentina, and Paraguay meet, faces significant challenges due to the complexity of socio-cultural, economic, and political contexts. The region is characterized by cultural diversity and structural inequalities that directly impact the implementation of public health policies. Gender issues play a central role in this scenario, influencing access to health services, reproductive rights, and perceptions of sexuality among men and women. The objective of this study was to identify the challenges and influences of gender issues in the implementation of sexual and reproductive health education programs in the Triple Frontier region. The study is an integrative review, with online research from LILACS, BVS, PUBMED, and Scielo databases, using the following descriptive terms: "Health education", "Sexual and reproductive health", "Border", "Gender" from the last 5 years. It was identified that the challenges faced in the implementation of sexual and reproductive health education programs in the Triple Frontier region are strongly intertwined with gender issues and the socio-cultural, economic, and political particularities of the involved countries. Gender inequality, reinforced by stereotypes and traditional social norms, limits equal access to information and health services, especially for women and girls, who continue to be the most vulnerable to institutional and cultural barriers.